Frequency and Patterns of Nail Changes in Psoriasis Vulgaris Patients Reporting to Civil Hospital Karachi - Mirza, Reema; Talat, Humaira; Mohanlal, Deepa; Imran, Tayyaba; Sajid, Madiha; Mansoor, Maria (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVES: To determine the frequency of nail changes in Psoriasis Vulgaris patients and to document the patterns of these nail changes in patients reporting to Civil Hospital Karachi (a tertiary care hospital). METHODOLOGY: This cross-sectional study was carried out at Dermatology Department – Civil Hospital Karachi from January 2017 – June 2018. The study included 100 clinically diagnosed cases of Psoriasis Vulgaris of either sex. The patients were enrolled irrespective of age, family history, duration and severity of disease. These patients were either admitted in ward or presented in OPD of Civil hospital Karachi. A detailed dermatological examination of these patients was carried out. The results were recorded in preformed pro-forma. RESULTS: The study concluded that out of a total of 100 patients of Psoriasis Vulgaris, there were 54 (54%) males and 46 (46%) females. 79 (79%) patients had nail changes while remaining 21 (21%) had normal nails. Nail ridging was found in 75 (94.93%), pitting in 70 (88.6%), discoloration in 70 (88.6%), onycholysis in 60 (75.94%), subungual hyperkeratosis in 56 (70.88%) of patients. Other nail findings included paronychia, twenty nail dystrophy, Beau’s lines, longitudinal melanonychia, shiny nails and splinter hemorrhages. CONCLUSION: Nail changes are common Psoriasis Vulgaris. Nail ridging, pitting, discoloration being the most common. Other findings included onycholysis, oil drop sign, subungual hyperkeratosis, paronychia, twenty nail dystrophy, beau’s lines and splinter hemorrhages. KEYWORDS: Nail Abnormalities; Psoriasis.